2009
DOI: 10.3122/jabfm.2009.06.090040
|View full text |Cite
|
Sign up to set email alerts
|

Increased Osteoporosis Screening Rates Associated with the Provision of a Preventive Health Examination

Abstract: Objectives:We determined the frequencies of (1) female patients aged 65 years and older having bone density measurement performed and (2) prescription therapy use among osteoporotic women.Methods: We completed a retrospective chart audit to assess our adherence to Physician Quality Reporting Initiative guidelines. Women aged 65 to 75 with an office visit between June 1 to November 30, 2007, were divided into 3 subgroups: those who had a recent preventive general medical examination (GME), those who received on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
2
7
1
Order By: Relevance
“…In patients who have not sustained a previous fragility fracture, adding osteoporosis screening questions to a preventative health examination with general physical examination can significantly increase (96%) the rate of osteoporosis screening. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients who have not sustained a previous fragility fracture, adding osteoporosis screening questions to a preventative health examination with general physical examination can significantly increase (96%) the rate of osteoporosis screening. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The number was lower than expected when compared to previous studies that have shown up to 58% taking appropriate medication. 22 However, there have been reports of treatment rates of osteoporosis as low as 2% after hip fractures. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Grover et al 8 found high rates of screening and treatment for osteoporosis among older women who received a general preventive examination compared with those who did not. More evidence supporting the recommendation of a routine physical is needed to encourage completion of needed prevention items.…”
Section: -13mentioning
confidence: 99%
“…Looks like a typical day in the family medicine office! Although most of the authors are from university family medicine departments and residency programs, [1][2][3][4][5][6][7][8][9][10] we also welcome contributions with implications for primary care from others outside the field.…”
Section: A Typical Day In the Family Medicine Officementioning
confidence: 99%
“…This study makes a good argument to have a registry or an electronic medical record that allows us to audit our work. At the Mayo Clinic, Grover et al 3 had such a registry; however, we audit our osteoporosis patients' charts using electronic billing reports that are easily queried and with the paper record; this shows it can be done without an electronic registry.…”
Section: Re: Increased Osteoporosis Screening Rates Associated With Tmentioning
confidence: 99%